The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jafc.9b01687
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Pathways Behind the Effects of Nutrients and Dietary Polyphenols on Gut Microbiota and Intestinal Permeability: A Perspective on the Potential of Metabolomics and Future Clinical Applications

Abstract: The gastrointestinal tract hosts the largest microbial population of the human body, which works in symbiosis with the host to provide several important functions and contributes to the maintenance of host health. The diet is one of the factors that can most affect the gut microbiota, with subsequent consequences on host health. One consequence of changes in microbiota is changes in intestinal permeability (IP); disruption of this latter is related to the development of several diseases and is a frequent condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 85 publications
(181 reference statements)
3
40
0
Order By: Relevance
“…Through the administration of the selected foods, we provided mainly flavonoids (approximately four times higher compared to the amount introduced through the C-diet) and phenolic acids. These bioactives have been suggested as potential modulators of critical factors and specific targets regulating IP, including the impact on microbiota composition and activities [15,41]. Overall, our results demonstrate that it is possible to obtain a significant increase in polyphenol intake in older subjects, through the use of small amounts of well-accepted polyphenol-rich food products.…”
Section: Discussionsupporting
confidence: 54%
“…Through the administration of the selected foods, we provided mainly flavonoids (approximately four times higher compared to the amount introduced through the C-diet) and phenolic acids. These bioactives have been suggested as potential modulators of critical factors and specific targets regulating IP, including the impact on microbiota composition and activities [15,41]. Overall, our results demonstrate that it is possible to obtain a significant increase in polyphenol intake in older subjects, through the use of small amounts of well-accepted polyphenol-rich food products.…”
Section: Discussionsupporting
confidence: 54%
“…On the one hand polyphenols can modulate the composition of microbiota; on the other hand, the microbiota is able to metabolize them into bioactive compounds. However, it seems clear that correct eating habits, typical of the Mediterranean diet, characterized by a high intake of polyphenols, play an important role in the maintenance of intestinal functions (76).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that selected strains of bacteria can positively influence the gut barrier [ 16 , 17 ]. Moreover, it is suggested that food components can strengthen the integrity of the gut barrier, mostly by affecting the gut microbiota and restoring the microbial homeostasis [ 18 , 19 , 20 ]. Therefore, prebiotics, the substrates that are selectively utilized by host microorganisms conferring a health benefit [ 21 ], were proposed as a promising intervention for gut barrier improvement [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%